2014
DOI: 10.1177/0363546514532226
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Based Differences in the Clinical Presentation of Patients With Symptomatic Hip Labral Tears

Abstract: Male and female patients differ in their hip structure, biomechanics, and operative findings of symptomatic labral tears. However, they do not differ substantially in clinical presentation, except that males are more likely to report an acute injury and females are more likely to be evaluated with increased range of motion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 19 publications
1
21
0
1
Order By: Relevance
“…1,7 Dierckman et al 7 reported an inverse relationship between duration of symptoms and minimum 2-year outcomes; furthermore, Aprato et al 1 noted that patients who had symptoms for >3 years had inferior outcomes and were more likely to require a revision. In this study, we found that female and male patients had comparable outcomes, which is consistent with a study by Lindner et al 27 Those authors analyzed a cohort of 1401 patients and determined that there was no significant difference between men and women in their clinical presentation, except that women had increased range of motion and men were more likely to report an acute injury. However, this analysis showed that women were more likely to convert to THA.…”
Section: Discussionsupporting
confidence: 91%
“…1,7 Dierckman et al 7 reported an inverse relationship between duration of symptoms and minimum 2-year outcomes; furthermore, Aprato et al 1 noted that patients who had symptoms for >3 years had inferior outcomes and were more likely to require a revision. In this study, we found that female and male patients had comparable outcomes, which is consistent with a study by Lindner et al 27 Those authors analyzed a cohort of 1401 patients and determined that there was no significant difference between men and women in their clinical presentation, except that women had increased range of motion and men were more likely to report an acute injury. However, this analysis showed that women were more likely to convert to THA.…”
Section: Discussionsupporting
confidence: 91%
“…Hetsroni et al 49 assessed sex differences in the clinical presentation of patients with hip labral pathology and, in a cohort of 105 male patients and 67 female patients, found that female patients had significantly smaller alpha angles, acetabular version values, and femoral anteversion values compared with male patients and stated that, in female patients, cam deformities may be more subtle. In a similar study, Lindner et al 50 speculated that female patients may, at baseline, have a greater component of soft-tissue (capsular) laxity, contributing to their overall symptoms.…”
Section: Discussionmentioning
confidence: 94%
“…Recent studies have reported on sex-based differences in clinical presentation of labral tears and femoroacetabular impingement. 24,31,41 In a prospective cohort of 654 patients, Lindner et al 31 noted that female patients had significantly increased range of motion, pain over the greater trochanter at presentation, and lower PRO scores compared with male patients. Nepple et al 41 prospectively analyzed 100 patients and found that female patients had more profound symptoms, as measured with multiple PRO instruments, and milder morphologic abnormalities.…”
Section: Discussionmentioning
confidence: 99%